Performance of mixed matrix nanofiltration membranes in wastewater treatment: A review. Issue 1 (April 2021) - Agboola, O.; Fayomi, O.S.I.; Oni, B.A.; Ayeni, A.O.; Sadiku, E.R.; Popoola, A.P.I.; Moropeng, L.; Adegbola, S.T.; Daramola, D.
Abstract: Water covered close to 70% of the Earth's surface; however, it is a struggle to access 3% of it as freshwater, suitable for human intake. The shortage of water has become a global issue due to climate change, pollution and the demand of growing freshwater. The fabrication of high performance and antifouling nanofiltration membranes are of utmost importance as a result of their capability of treating contaminated water and to also regulate the quality of freshwater. However, there is need for improvement in the fabrication of membrane using different nanofillers to produce mixed matrix membranes (MMMs). Mixed matrix nanofiltration membranes with nanofillers were reviewed for different applications.